Polymer physics - Rubinstein, Michael; Colby, Ralph H. (Oxford ; New York : Oxford University Press, 2003)
"This is a polymer physics textbook for upper level undergraduates and first year graduate students. Any student with a working knowledge of calculus, physics, and chemistry will be able to read this book. The essential tools of the polymer physical chemist or engineer are derived in this book without skipping any steps. The book is a self-contained treatise that could also serve as a useful reference for scientists and engineers working with polymers. While no prior knowledge of polymers is assumed, the book goes far beyond introductory polymer terms in the scope of what is covered. The fundamental concepts required to fully understand polymer melts, solutions and gels in terms of both static structure and dynamics are explained in detail.
Includes bibliographical references and index.
Keywords: Polymers; Polymerisatie; Fysische eigenschappen; Thermodynamische eigenschappen; Vloeibare kristallen; Viscositeit; Chemische structuur; Vastestoffysica; Polímeros (materiais); Physik; Polymere